ROLE OF DRAVIDIAN PARTIES FOR WOMEN'S WELL-BEING - P. Pavithra (RADJA PUBLIKA, 2022)
Abstract Women's welfare refers to their happiness and general happiness. Obstacles to women's advancement include untouchability, child marriage, and caste oppression. Leaders like Nathuram Jyotiba Poole, Eeswara Chandra Vidyasagar, Mahatma Gandhi, and others rescued the female community. The DMK government enacted laws for women's advancement, implemented programs, and defended education and employment rightsThe DMK government passed a law in 1921, giving women the right to vote, symbolizing justice and progress. As women progress, they will be empowered to question society's crimes and prevent social crimes.